Biblical vistas of brokenness and wholeness in a time such as the coronavirus pandemic - Dames, Gordon Ernest (HTS teologiese studies, 2020)
In the midst of the coronavirus (COVID-19) pandemic, new unexpected and extraordinary scenes and sounds of aesthetical biblical and apocalyptic proportions are witnessed. Community and religious gatherings in public spaces are prohibited. Modern, conventional and traditional human achievements have become futile. One can describe the COVID-19 pandemic, and this new search for meaning as a juxtaposed tension of metaphorical apocalyptic vistas and metaphorical biblical vistas. The Bible holds the same juxtaposed tension which may help humanity to rediscover the semantics of biblical truth and hope – but it also espouses a metaphorical liberational vista of transcendence. Coronavirus could be a metaphor for something with extraordinary new possibilities. The biblical metaphors are being amplified in different metaphorical vistas to make it more discerning or accessible to the world population today. As a metaphorical liberation vista, it may offer new hope for a new kind of living, a new kind of humanity, a new kind of knowing and believing and a new kind of world order.Contribution: This article offers a Practical Theological contribution to the significance of the Bible within the COVID-19 pandemic context. Human suffering and divine metaphorical vistas encapsulate prospects for truth, hope and new meaning for the liberation of humanity.